Métodos para identificação de moléculas com atividade herbicida com ênfase na rota de síntese de carotenóides - Corniani, Natália [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Weed management has always been an important aspect of crop production. The introduction of synthetic herbicides in the mid-20th century has made weed control less expensive and more effective. The introduction of transgenic crops resistant to non-selective synthetic herbicides (e.g., glyphosate and glufosinate) further established the reliance on herbicides as the dominant technology used for large-scale weed control in production agriculture worldwide. However, the selection pressure imposed by herbicides has led to the widespread evolution of herbicide resistance in weed populations, which is a major threat to the sustainability and profitability of cropping systems. Reliable tests for resistance are an essential pre-requisite for the rational implementation of effective integrated control strategies. There is increasing demand from growers to test for weed resistance and learn how to manage it. Scientists have developed resistance-testing protocols for numerous herbicides but, in Brazil, there is no review compiling this information. Evolution of herbicide resistance is also underscoring the need for herbicides with new modes of action to complement those herbicides failing due to resistance. The 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway represents one of the most promising targets to develop new herbicides as well as targets to improve the nutritional value of crop plants. However, there is just one commercial herbicide, clomazone, targeting it. Therefore, in the first chapter of this study there is a compilation of assays to measure the activity of key target enzymes and characterization of plant resistance to all known herbicides mode of action. Since no in vivo assay was available for testing inhibitors of MEP pathway, in the second chapter it is described the development of a rapid, accurate, cheap, readily available leaf disc assay based on the measurement of the carbon ...

O manejo de plantas daninhas é um aspecto importante da produção agrícola. A introdução de herbicidas sintéticos, em meados do século 20, tornou o controle de plantas daninhas menos dispendioso e mais eficaz. A introdução de culturas transgênicas resistentes a herbicidas não-seletivos (por exemplo, glifosato e glufosinato) reforçou o estabelecimento dos herbicidas como a principal tecnologia usada para controle em grande escala de plantas daninhas na produção agrícola mundial. No entanto, a pressão de seleção imposta pelos herbicidas levou à evolução generalizada de resistência em populações de plantas daninhas, o que representa uma grande ameaça para a sustentabilidade e rentabilidade dos sistemas de cultivo. Testes confiáveis para a detecção de resistência são pré-requisito para a implementação de estratégias de controle integrado eficazes. Há demanda crescente dos produtores por testes para diagnosticar a resistência de plantas daninhas e aprender a gerenciá-la. Os cientistas desenvolveram protocolos de teste de resistência para inúmeros herbicidas, mas, no Brasil, não há nenhum trabalho compilando essas informações. A evolução da resistência tem também acentuado a necessidade de produtos com novos mecanismos de ação para complementar a falta de atividade dos herbicidas atuais. A rota do metileritritol fosfato (MEP) representa um dos alvos mais promissores para o desenvolvimento de novos herbicidas, bem como para melhorar o valor nutricional de culturas agrícolas. No entanto, há apenas um herbicida comercial, clomazone, alvejando esta rota. Portanto, o primeiro capítulo do presente trabalho consiste em uma compilação de ensaios para medir a atividade de enzimas-alvo e caracterização de resistência de plantas a todos os modos de ação de herbicidas conhecidos. Uma vez que não havia descrito nenhum ensaio in vivo para testar ...
Keywords: Resistência a herbicidas; Erva daninha; Carotenoides; Weeds